The new party politics of the European Union: Evidence from the EP Political Groups' votes on the Mediterranean migration crisis after the Lisbon Treaty reform of the European Council - Fulvio Attinà (European Institute of Romania, 2019)
The present paper draws the attention of political scientists towards the participation of the European Parliament in EU legislation making on migration and in the EU management of the migration crisis of the last seven years. The paper aims at knowing whether and, in the positive case, why the members of the Parliament mainly backed the management decisions and actions of the EU Council, Commission, and member governments in response to the inflow of refugees and irregular migrants. The analysis of the EP votes demonstrates that the mainstream Political Groups, namely the PGs of national mainstream parties, play as the passive legitimizers of the decisions of the European Council and the Commission. They are qualified as the passive legitimizers because the MEPs of the national mainstream parties share the policy their country government leaders adopt in the European Council towards restricting immigration. In other terms, the MEPs and the government chiefs of the mainstream national parties share the interest of being re-elected by the anti-immigration voters.
Keywords: 330; European Parliament; Political Groups; Migration; Party Politics